2006
DOI: 10.1038/sj.emboj.7601276
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating the dual roles of apoptosis-inducing factor in maintaining mitochondrial structure and apoptosis

Abstract: The mitochondrial protein apoptosis-inducing factor (AIF) translocates to the nucleus and induces apoptosis. Recent studies, however, have indicated the importance of AIF for survival in mitochondria. In the absence of a means to dissociate these two functions, the precise roles of AIF remain unclear. Here, we dissociate these dual roles using mitochondrially anchored AIF that cannot be released during apoptosis. Forebrain-specific AIF null (tel. AifDelta) mice have defective cortical development and reduced n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
171
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(178 citation statements)
references
References 57 publications
3
171
1
1
Order By: Relevance
“…While excitotoxic cell death also converges on mitochondria, the upstream signalling events are quite distinct. We and others have shown that this mode of cell death occurs independent of Bax/Bak because deletion of these proteins does not affect the rate of cell death [8][9][10]. During acute brain injury such as stroke, oxygen levels are reduced, which leads to an abrupt decrease in ATP production and rapid depolarization of the plasma membrane which occurs early after the ischemic insult in stroke.…”
Section: Overview Of Neuronal Cell Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…While excitotoxic cell death also converges on mitochondria, the upstream signalling events are quite distinct. We and others have shown that this mode of cell death occurs independent of Bax/Bak because deletion of these proteins does not affect the rate of cell death [8][9][10]. During acute brain injury such as stroke, oxygen levels are reduced, which leads to an abrupt decrease in ATP production and rapid depolarization of the plasma membrane which occurs early after the ischemic insult in stroke.…”
Section: Overview Of Neuronal Cell Deathmentioning
confidence: 99%
“…Apart from the apoptotic role of AIF following its release and translocation to the nucleus [3,[139][140][141][142], AIF also has a physiological Fig. 4 During excitotoxicity, elongated mitochondria along the neurite and at the synapse can buffer Ca 2+ more effectively than fragmented mitochondria.…”
Section: Mitochondrial Cristae Structure and Cell Death: Demolition Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found that caspase-3-mediated events appeared to be dispensable in determining the overall killing of cells, since 50 kb DNA fragments, chromatin condensation, Rb, gelsolin, and poly (ADP-ribose) polymerase (PARP) cleavage also occurred in caspase-3-deficient MCF-7 cells [19][20][21] . When caspase-3 has no contribution to cell death, cells can still die apoptotically by non caspase-3-dependent or caspase-independent mechanisms due to the activation of other effective caspases or the nuclear translocation of AIF [22] .…”
mentioning
confidence: 99%
“…5 This is similar to AIF and HtrA2, which could impair mitochondrial function when released into the cytosol. 31,32 In addition, studies have shown that mitochondria can themselves release controlled amounts of cytochrome c, Smac, HtrA2, and AIF, by a still-unclear mechanism. 33,34 Inhibitors of caspase -1 and -3 modify LTP of synaptic transmission in hippocampal synapses, 35,36 indicating functions for apoptotic cascades in synaptic plasticity.…”
Section: Apoptosismentioning
confidence: 99%